MANAGEMENT OF THE POLITICAL PARTY INFORMATION SYSTEM (SIPOL) APPLICATION AT THE INDEPENDENT ELECTION COMMISSION, BANDA ACEH - Hidayat, Rachmat; Yusri Razali; Nanda Ermanda; Kurnia (STMIK Indonesia Banda Aceh, 2026)
The Political Party Information System (SIPOL) application functions as a supporting tool to facilitate decision-making, ensure data organization, enable data collection, storage, distribution, and provide access to information. The involvement of Information Technology (IT) through the SIPOL Management Information System (MIS) in the verification process of political parties reflects the digitalization of electoral stages, producing adaptive and modern verification of party documents toward efficiency and effectiveness. The writing method employed combines a qualitative descriptive approach, based on experiences and observations during the 2024 General Election, with a quantitative descriptive statistical approach to determine the extent of SIPOL’s role in effectively and efficiently verifying political parties. The findings indicate that the SIPOL application plays a strong and dominant role in realizing organizational integration and coordination, knowledge and learning management, risk management and compliance, as well as supporting decision-making. Furthermore, SIPOL demonstrates a very strong and highly dominant role in enhancing efficiency and productivity, as well as improving collaboration and communicatio